Chronicle of a demise foretold: state vs. local groundwater management in Texas and the high plains aquifer system - Closas, Alvar; Molle, Francois (2018)
This paper assesses a case of co-management of groundwater between the state of Texas, pushing for the rationalisation of groundwater management, and local (mainly farming) communities organised in Groundwater Conservation Districts (GCDs), which are protective of their private groundwater rights. We first describe the main legal and policy steps that have shaped this relationship. The article focuses on the Texan portion of the Ogallala Aquifer in the High Plains aquifer system – an almost non-renewable system covering 90,000 km2 and providing 95% of the irrigation needs in northern Texas. With this example, we further highlight the strategies of both parties, the different political, administrative, legal and regulatory complexities of the struggle around the definition of GCD-level aquifer management rules (the so-called 'Desired Future Conditions'). We end by reflecting on the power balance that has resulted from successive adjustments to a co-management form of governance, the advantages and disadvantages of a multi-layered state water governance system, and whether the de facto 'managed depletion' of the Ogallala Aquifer in Texas should be seen as an achievement or a failure.